2022
DOI: 10.5194/bg-2022-217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographical controls and anthropogenic impacts on dissolved organic carbon from mountainous rivers: Insights from optical properties and carbon isotopes

Abstract: Abstract. Mountainous rivers (MRs) are one of the critical systems in transporting dissolved organic carbon (DOC) from terrestrial environments to downstream ecosystems. However, how geographical factors and anthropogenic impacts control the composition and export of DOC in mountainous rivers remains largely unclear. Here, we explore DOC dynamics in three subtropical mountainous catchments (i.e., the Yinjiang, Shiqian, and Yuqing catchments) in southwest China which are highly influenced by anthropogenic activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Moreover, Chen et al . [ 83 ] recently suggested that even in mountainous rivers in-stream production and transformation of carbon exerts a significant influence on riverine DO 14 C dynamics. Riverine in-stream transformations can be separated into biotic (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Chen et al . [ 83 ] recently suggested that even in mountainous rivers in-stream production and transformation of carbon exerts a significant influence on riverine DO 14 C dynamics. Riverine in-stream transformations can be separated into biotic (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…primary and secondary production) or abiotic (e.g. absorption, desorption, photo-oxidation, dissolution) processes, which are each strongly controlled by river water temperature and residence time [ 33 , 35 , 83 ]. The significant positive relationship between DO 14 C and the long-term average of annual river water temperature from the NADUF dataset supports the assumption of significant in-stream productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations